Should Anyone Care about Scientific Progress?. Issue 1 (January 2021) - Sassower, Raphael
Scientific progress has been understood as synonymous with the growth of knowledge and the advancement of humanity. In this brief survey, this concept is problematized both in rhetorical terms and within the neoliberal framework. Despite the sustained marketing of the scientific community and its funding agencies, the dangers associated with progress are explained and highlighted.